Antibodies against Gonadotropin-Releasing Hormone in Patients with Posterior Laryngitis - Hillevi Pendleton; Ragnar Alm; Gunilla Nordin Fredrikson; Bodil Ohlsson (AboutScience Srl, 2013)
Patients with functional gastrointestinal disorders express antibodies against gonadotropin-releasing hormone (GnRH) in serum. One common cause of posterior laryngitis (PL) is extra-esophageal reflux, but a functional etiology has also been suggested. The aim of this study was to scrutinize patients with PL with regard to the presence of GnRH antibodies and to examine the association between antibodies and symptoms and reflux. Consecutive PL patients were included after examination. Serum was analyzed for the presence of antibodies using an enzyme-linked immunosorbent assay (ELISA) method and expressed as relative units (RU). Two age- and gender-matched healthy subjects per case served as controls. The prevalence of IgM GnRH antibodies in patients was 35% compared with 28% in controls ( P = 0.06), with higher levels in patients (0.8 (0.3-2.2) RU) than in controls (0.2 (0.1-0.6) RU) ( P = 0.007). The corresponding IgG antibody prevalences were 43% and 4%, respectively ( P = 0.001), with no difference in levels ( P = 0.70). There was no association between antibodies and clinical findings.